2017
DOI: 10.18768/ijaedu.309803
|View full text |Cite
|
Sign up to set email alerts
|

ANALYZING THE UTILITY OF GRAMMAR TRANSLATION METHOD & DIRECT METHOD FOR TEACHING ENGLISH AT INTERMEDIATE LEVEL

Abstract: English is considered as fascinating and laureates' language in Pakistan. It has also become a status symbol in our society. Pakistani learners are facing difficulty while studying English because they are not taught English as a skill rather as a subject. For the benefits of students, language teachers had a thrust to invent new methods to satisfy their students' needs. The current study was designed to explore the utility of combination of grammar translation method and direct method for teaching English at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…GTM dominated European and foreign languages from the 1840s to the 1940s (Anabokay & Suryasa, 2019). It started in Germany, specifically in Prussia, at the end of the eighteenth century (Bhatti & Mukhtar, 2017). The main focus of GTM is translating sentences from the native language to the target language and vocabulary (memory & translation).…”
Section: Literature Review 21 Grammar-translation Methods and Direct ...mentioning
confidence: 99%
See 2 more Smart Citations
“…GTM dominated European and foreign languages from the 1840s to the 1940s (Anabokay & Suryasa, 2019). It started in Germany, specifically in Prussia, at the end of the eighteenth century (Bhatti & Mukhtar, 2017). The main focus of GTM is translating sentences from the native language to the target language and vocabulary (memory & translation).…”
Section: Literature Review 21 Grammar-translation Methods and Direct ...mentioning
confidence: 99%
“…Even though it is believed that the Direct method is more efficient than the Grammar Translation method, many studies have shown that both need to be used in the classroom to ensure students' learning and those teachers should strive to find activities that will not bore their students and often those activities may belong to a few different teaching methods. (Bhatti & Mukhtar, 2017;Djauhar, 2021).…”
Section: Literature Review 21 Grammar-translation Methods and Direct ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the low English-speaking skill performed by students, many teaching approaches or methods emerged from time to time, such as the Audio-Lingual Method, Total Physical Response, and Communicative Language Teaching. In response to it, there are lots of researches in ELT that utilize those methods in numerous settings beneath the same concern (Bhatti & Mukhtar, 2017;Fazil et Journal on English as a Foreign Language,12(1), 74-96 p-ISSN 208874-96 p-ISSN -1657e-ISSN 2502e-ISSN -6615 al., 2018Mart, 2013;Toro et al, 2018;Yuliani, 2018); it is done to assist students' development in their English skills. Speaking skills in the English language is an essential skill needed to be mastered.…”
Section: Introductionmentioning
confidence: 99%
“…The result of this study showed that the teachers mostly implemented GTM rather than DM, but they have a positive perception of this implementation and argued and assumed that the DM is interesting to be implemented. On the other hand, GTM and DM are assumed better if those are combined at the same time in the learning process (Bhatti & Mukhtar, 2017).…”
Section: Introductionmentioning
confidence: 99%